IMPLEMENTASI STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN DI SMP NEGERI 1 SUNGAI RAYA KABUPATEN KUBU RAYA - Lamazi, Lamazi; Amin, Maswardi M; Chiar, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract  The purpose of National Education is to develop the quality of human resources as early as possible in a directional, integrated and comprehensive through various productive and creative efforts by all components of the nation, so that young people can develop optimally. Personnel directly related to the task of providing education is Educators and Education Personnel. The purpose of this study is to obtain descriptive information about the implementation of educator standards and education personnel focused on academic qualifications, physical and spiritual health of educators as well as their competence, academic qualifications and leadership capabilities of the headmaster. With a qualitative approach and case study, this thesis is prepared using primary and secondary data through interview, observation and documentation. Data analysis uses data reduction, presentation, and conclusions. The study found that; educators' academic qualifications meet the standards, the physical and spiritual health of educators, the competence of educators is also good, the academic qualifications of the headmaster have been very feasible, and this certainly has implications on the leadership capability.  Keywords: Implementation, Standard, educators and education personnel